CEO Power and Audit Quality: Does Monitoring Intensity Matter? - Alyafai, Ayoob (Curtin University, 2021)
The thesis examines whether chief executive officers (CEOs) use their power to influence audit quality, proxied by audit fees and the likelihood of receiving a going-concern opinion. In addition, this thesis examines the moderating role of internal and external monitoring on the association between CEO power and audit quality to assess whether monitoring intensity can counterbalance CEO power. The findings of this study have several implications for regulators, auditors, investors, and academic researchers.